Digital media reveal negative impacts of ghost nets on Brazilian marine biodiversity - Azevedo-Santos V.M. (2021)
© 2021 Elsevier LtdAbandoned, lost, or otherwise discarded fishing gear (ALDFG) is responsible for the entanglement of several marine species. Based on a search of digital media (i.e., Google and YouTubeBR), we assessed the negative impacts of ghost nets—a type of ALDFG—on Brazilian marine biodiversity. We found that ghost nets negatively affected crustaceans, fishes, reptiles, birds, and mammals in different parts of the Brazilian coast. Our reports include marine megafauna, such as the Bryde's whale and Guiana dolphin. In addition, we found that ghost nets impacted seven threatened species and had negative effects on animals within marine protected areas. Here, we provide an update on the negative impacts of ghost nets on Brazilian marine biota, but the real situation remains underestimated and somewhat obscure.